The Influence of Processed Steel Slag Additive on Brick-Making Clay - Loncnar, Mojca; Tominc, Sara; Žibret, Lea; Mrak, Maruša; Ducman, Vilma (8th International Conference on Technologies & Business Models for Circular Economy: Conference Proceedings, 2026)
As clay deposits become scarce, the brick industry is increasingly seeking additives or substitutes. This study investigates a high-plasticity clay that requires an opening agent, for which was used 10 wt.% of processed steel slag Ekominit S1. Ceramic-technological tests were performed to determine the compressive strength, density and porosity. The addition of Ekominit S1 increased the total porosity by 5% in samples fired at 950 °C, and by 4% in samples fired at 1050 °C, while the compressive strength decreased by 36% in the samples fired at 950 °C and by 38% in those fired at 1050 °C compared to the reference material. Although the mechanical properties were lower than those of the reference, the benefit is reduced shrinkage. The processed steel slag could be incorporated successfully into bricks, which would also reduce the environmental impact of this sector by using secondary products instead of virgin materials.